SETTLEMENT OF DEFAULT UNDER THE ISTIṢNĀ‘ AGREEMENT IN PRINTING BUSINESS IN SHIAH KUALA DISTRICT - Ridwan Nurdin (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2022)
Istiá¹£nÄ' contract is an agreement or sale and purchase agreement by order, between the buyer (mustaá¹£ni') and the maker (á¹£Äni') for an item that does not yet exist with certain specifications, and payment can be made in advance, through installments, or deferred until the time of collection of the goods. . Printing in Syiah Kuala District is a place for the production of unfinished printed goods, which are generally carried out by order (istiá¹£nÄâ€˜). As long as the istiá¹£nÄ' contract is running, it is possible for the parties to be negligent or not fulfill their obligations which lead to default. The problem in this research is what are the forms of default in the printing business in Syiah Kuala District and how the default is resolved in the istiá¹£nÄ contract in the printing business that occurs in Syiah Kuala District from an Islamic economic perspective. The purpose of this research is to find out the forms of default in the printing business in Syiah Kuala District and to find out the mechanism for the settlement of default in the istiá¹£nÄ contract in the printing business that occurred in Syiah Kuala District according to an Islamic economic perspective. To answer this question, the writer uses descriptive analysis research method with the type of field research (field research), where the data obtained comes from the results of primary, secondary and tertiary data as well as from observations and interviews compiled by the author. From the results of this study, it can be seen the forms of default by the parties. Forms of default committed by the printer include being late in completing the ordered goods and the negligence of the printing party so that the customer does not receive the ordered goods, while the default by the customer is not taking the ordered goods. The default is resolved through a path that is in accordance with the Islamic economic perspective, namely through the ulá¸¥u (peace) route.